2010
DOI: 10.1096/fasebj.24.1_supplement.723.19
|View full text |Cite
|
Sign up to set email alerts
|

Immune responses of mouse mucosal system to glycated and hydrolysed OVA

Abstract: Advanced glycation endproducts (AGEs) are created during the spontaneous reaction that occurs in the body and during protein processing. AGEs cause chronic hyperglycemia, contribute to vascular and renal dysfunction, and are potential antigens. Our recent work showed the mucosal immune system responses to naive, hydrolysed and glycated ovalbumin (OVA‐H, ‐G) gavages to Balb/C mice. There were no differences between groups in anti‐OVA IgG, IgA serum and fecal titers. Cultured B lymphocytes did not show differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Our experiments show that non-enzymatic glycosylation (glycation) of PA impacts murine immune response against PA. G-PA shows less immunogenicity as it induced a lower specific antibodies titers when compared to PA. These results are similar to those in one of our earlier studies, where we found that glycation has significant effect on the humoral responses elicited against ovalbumin . Probably, the attachment of glucose to albumins or aggregation of glycated proteins has changed availability of the conformational epitopes of PA, thus affecting the production of antibodies; however, this will require further investigations.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Our experiments show that non-enzymatic glycosylation (glycation) of PA impacts murine immune response against PA. G-PA shows less immunogenicity as it induced a lower specific antibodies titers when compared to PA. These results are similar to those in one of our earlier studies, where we found that glycation has significant effect on the humoral responses elicited against ovalbumin . Probably, the attachment of glucose to albumins or aggregation of glycated proteins has changed availability of the conformational epitopes of PA, thus affecting the production of antibodies; however, this will require further investigations.…”
Section: Resultssupporting
confidence: 91%
“…These results are similar to those in one of our earlier studies, where we found that glycation has significant effect on the humoral responses elicited against ovalbumin. 33 Probably, the attachment of glucose to albumins or aggregation of glycated proteins has changed availability of the conformational epitopes of PA, thus affecting the production of antibodies; however, this will require further investigations. Since the humoral response to PA was found to be greater than that to G-PA, we used PA for immunization of mice to check for cellular immune response.…”
Section: ■ Results and Discussionmentioning
confidence: 99%